Analysis of Energy Evolution Characteristics of Salt Rock Under Different Loading Rates - Wang, J. B.; Liu, X.; Zhang, Q.; Song, Z. P. (Frontiers in Earth Science, 2022)
The existing uniaxial compression test results of salt rock under different loading rate is used to study its energy evolution characteristics during deformation and failure in this paper. First of all, the influence of loading rate on the total energy density, elastic energy density and dissipated energy density is analyzed. Afterwards, the relationship between the number and size of fragments, crushing intensity after rock destruction and energy density of each part is discussed. The results show that the energy evolution process of salt rock during deformation and failure contains three stages: namely, energy accumulation stage, energy dissipation stage and energy release stage. With the increase of loading rate, the total energy density and dissipated energy density gradually decrease, while the elastic energy density increases. When the volume of rock remains constant, the greater the dissipated strain energy, the more the number of fragments will be produced after rock failure. When the dissipated strain energy remains unchanged, the larger the dissipated strain energy (surface free energy) is, the smaller the number and the larger the size of fragments will be produced. When the total strain energy is constant, the splash rate of the fragments increases with increasing elastic strain energy ratio.